The fate of human enteric pathogens following the land application of biosolids in agriculture - Schwarz, Karen Rosemary (Curtin University, 2012)
A research project was undertaken to study the effect of biosolids on the decay times of enteric pathogens in the soil. This is the most comprehensive study in Australia where the persistence of enteric microorganisms in land-applied biosolids, particularly on broadacre grain farms in Australia, has been studied.Enteric pathogens such as faecal bacteria and viruses are present in biosolids, and when applied to land, these disease-causing microorganisms are at risk of being transmitted to humans following contact. The main aim of this research project was to examine the decay times of Escherichia coli (an indicator of enteric bacterial pathogens), Salmonella enterica (a representative of human pathogenic bacteria), bacteriophage MS2 (surrogate virus) and adenovirus (a representative human pathogenic virus). Agricultural soil from two farming properties in Western Australia and South Australia was selected for testing the inactivation of these enteric microorganisms over the growing season of a cereal crop. To do this, soil, biosolids and human enteric microroganisms were inoculated into sentinel chambers and inserted into the soil in the field. Chambers were sampled at regular intervals across the duration of the experiment and pathogen numbers were plotted over time. The decay times (T90) were then calculated based on the slope of decay to determine the estimated time for a one-log10 removal to occur.The key findings from the soil (field) experiments were that a) very low numbers of bacteria and bacteriophage (MS2) were detectable in the soil by harvest time since the microorganisms decayed rapidly over the growing season of the crop and b) that the decay times for E. coli, S. enterica and MS2 were shorter in the biosolids-amended soil compared with the unamended soil. Results indicated that the application of biosolids to the soil may have actually increased the inactivation processes of the enteric microorganisms in the soil. Further findings were that enteric microorganism numbers, particularly bacteria, were significantly correlated with the changes in soil moisture and bacteriophage MS2 was significantly correlated with changes in soil temperature. For industry, this means that while the application of biosolids may introduce harmful pathogens to the field, the pathogens (in biosolids-amended soils) are adequately reduced over time. In addition, the climatic conditions as typical for Australia with dry hot summers, generally do not favour the survival of enteric pathogens.A glasshouse experiment was conducted to validate the methodology for the quantification and enumeration of enteric microorganisms from soil and biosolids-amended soil. The resulting methods were a combination of procedures and processes from several sources that proved successful to improve the recovery of microorganisms from manure, biosolids or soil samples. The data from this experiment highlighted the difficulty faced when fitting a linear line of regression to the observed data points in order to calculate the time taken for the reduction of microorgainsms or the decay times (T90 values) from the reciprocal of the slope. Because of this, statistical models that take curvature into account with more terms such as quadratic and cubic were examined. The quadratic model was observed to provide the best fit, therefore was considered the most suitable for use for the field (soil) data.A phyllosphere experiment was conducted to determine the decay times of enteric microorganisms on the leaves, spikelets (grain heads) and grains of wheat. This was important where fodder crops are grown for livestock feed in biosolids-amended paddocks. The concern was that pathogenic contaminants would transfer from the soil to the plant and be of risk at consumption. A key finding from the present study was that enteric microorganisms were detectable for longer in the soil (6 to 7 months) than the plant leaves (less than 1 month) therefore enteric pathogens on plant leaves would be of most risk to livestock where crops such as hay or lucerne are grown. Where withholding periods are maintained the risk of pathogen ingestion was considered to be low. Given favourable weather conditions for hay and silage production, the time from cutting to baling is approximately 1 week and because of this, the risks to livestock from pathogens is also considered low. Although the bacteria and virus examined in this research survived for several months on wheat grains (i.e. the time for a one-log10 removal (T90) for bacteria on stored grains was 9 to 12 d), the risks to humans was considered to be low based on the assumption that grains are often milled, ground and baked prior to consumption.Thresher and dust studies were conducted to compare indigenous bacterial levels at sites where biosolids had been applied, with sites where no biosolids had been applied. A key finding was that indigenous heterotrophic bacteria and enterococci numbers were higher at the biosolids-amended harvesting site than the unamended site. In addition, the highest numbers of bacteria (and inoculated microorganisms) was found on the chaff, indicating that this region could be sampled for the testing of any pathogenic microorganisms potentially present in dust samples. Results demonstrated that the process of threshing significantly reduced microorganism numbers on matured wheat plants. For industry this means that the risk of transferring human enteric pathgoens (bioaerosols) to humans at harvest time is low where crops have been previously applied with biosolids (particularly if field workers remain inside vehicles in sealed cabs of harvesters, trucks and utes or use dust protection while the harvester is in operation). In addition, the high summer temperatures, dry conditions and low humidity in the field at harvest time do not favour the prolonged survival of bioaerosols.This study provides scientific data on the survival patterns of enteric bacteria and viruses across the growing season of wheat when introduced into agricultural soil from land-applied biosolids. The practical application of the results to cereal production enables key stakeholders to consider the areas of risk across the supply chain of grain production to contribute towards consumer safety and public protection. It was concluded that pathogens from biosolids are of greatest risk to humans directly involved with the handling of biosolids following dispatch from the wastewater treatment plant since microbial contamination levels are highest during this time. In addition, the Australian climate is not suited to prolonged survival of enteric pathogens outside of the host, particularly from spring to summer where soil moisture declines and soil temperatures increase. The pathways to ingestion are low where withholding periods are maintained and correct management procedures are followed such as the incorporation of biosolids with the soil within the appropriate timeframe. Therefore, the main pathway for the transmission of disease-causing pathogens to humans may be more prevalent where poor hygiene practices occur.